Effect Of Napthalene Mixture with Gasoline Fuel on Gasoline Engine Performance - Yuniarto Agus Winoko; Afifur Rohman (International Journal of Marine Engineering Innovation and Research, 2023)
Naphthalene is a chemical hydrocarbon compound with the chemical formula C10H16O. Napthalene is a simple polycyclic aromatic hydrocarbon compound, in the form of a white crystalline solid with a characteristic odor and detectable by the sense of smell at concentrations as low as 0.08 ppm. As an aromatic compound, napthalene's structure consists of a pair of linked arene groups or benzene rings. Objective: To determine the ratio of the power produced by a gasoline engine using a mixture of naphthalene with 90 fuel compared to the use of pure fuel in the engine. Knowing the effect of exhaust emissions produced by gasoline engines using 90 octane fuel, with a mixture of naphthalene and without a mixture of naphthalene. The method used in this study was experimental, tested only with pertalite fuel, Pertamax and added camphor (Napthalene) consisting of 5gr, 10gr, 15gr with 2lt volume of 90 octane fuel fuel. The conclusion is expected that the addition of napthalene has an effect on power and exhaust emissions.